2012
DOI: 10.1161/atvbaha.111.224915
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cell Death in Heart Disease

Abstract: The major cardiac syndromes, myocardial infarction and heart failure, are responsible for a large portion of deaths worldwide. Genetic and pharmacological manipulations indicate that cell death is an important component in the pathogenesis of both diseases. Cells die primarily by apoptosis or necrosis, and autophagy has been associated with cell death. Apoptosis has long been recognized as a highly regulated process. Recent data indicate that a significant subset of necrotic deaths is also highly programmed. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
291
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 327 publications
(299 citation statements)
references
References 134 publications
5
291
1
2
Order By: Relevance
“…1 Traditionally, necrosis is regarded as a passive and unregulated cell death, while apoptosis has long been considered as the sole form of programmed cell death. However, emerging evidences suggest that a proportion of necrosis is regulated by serial signaling events in a controlled and orchestrated manner.…”
mentioning
confidence: 99%
“…1 Traditionally, necrosis is regarded as a passive and unregulated cell death, while apoptosis has long been considered as the sole form of programmed cell death. However, emerging evidences suggest that a proportion of necrosis is regulated by serial signaling events in a controlled and orchestrated manner.…”
mentioning
confidence: 99%
“…Myocardial infarction is generally caused by blood coagulate, that breaks the blood movement to the part of cardiac cells. 20 Treatment of myocardial infarction with clot-breaking medicine procedure is usually done to bring back the blood flow over the clogged blood vessel are commonly done. 21 The injured tissues of the heart in myocardial infarction can also be repaired by the replacement of damaged cells using stem cell therapy in cellular transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been demonstrated that the deletion of cardiomyocytes ultimately leads to HF (Olivetti et al, 1997). Nearly all types of HF are accompanied by increased cell death, attributed to stresses from circulating neurohormones, inflammation, oxidative stress, or toxins (Konstantinidis et al, 2012;Richter and Kostin, 2015). This leads to the release of growth factors which can result in the formation of fibrosis (Gandhi et al, 2011).…”
Section: Epidemiology and Pathophysiology Of Hfmentioning
confidence: 99%